Investment strategy and future performance: The moderating effect of ownership - Susanto, Idil Rakhmat; Soewarno, Noorlailie; Tjahjadi, Bambang (Business: Theory and Practice, 2024)
This study aims to investigate the Role of ownership structure on the Effect of investment strategy on future performance. The research focuses on ownership that compares foreign and domestic ownership structures. The research sample is a non-financial company in ASEAN countries. Multiple regression was performed to test the hypothesis using a financial dataset from 795 firm years of observation of non-financial companies in ASEAN. Our results show that foreign and domestic owners negatively affect the relationship between investment strategy and the future performance. The study’s results indicate that foreign and domestic ownership have no significant difference as a supporting factor for implementing the investment strategy in improving the company’s future performance. Our findings confirm the IO theory about implementing an investment strategy that affects future performance even though it impacts decreasing financial performance because companies need more time to see the impact of an investment strategy.